Literature Review: Risk Factors for Hypertension in the Coastal Area of Maginti Health Center - Rista Ekaputri; Ayu Listian (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Hypertension, or high blood pressure, is the leading cause of mortality worldwide, with 90–95% of cases classified as essential hypertension. Lifestyle factors play a significant role in its high prevalence, particularly among coastal populations. In addition to dietary patterns high in salt and fat, other unhealthy lifestyle behaviors such as smoking, physical inactivity, excessive coffee and alcohol consumption, poor sleep quality, and high stress levels can contribute to the development of hypertension. Objective: This literature review aims to identify and describe the risk factors contributing to the incidence of hypertension in coastal communities. Methods: Relevant research articles were retrieved using Google and Google Scholar, with the keywords “Hypertension,” “Coastal Areas,” and “Risk Factors.” The search was limited to studies published between 2020 and 2024, including both qualitative and quantitative research, available in PDF or full-text format, and published in either Indonesian or English. A total of 13 articles met the inclusion criteria and were analyzed. Results: The review identified several significant risk factors associated with the incidence of hypertension in coastal areas, including high-salt and high-fat dietary patterns, sedentary lifestyles, smoking, and other behavioral determinants. Conclusion: Lifestyle factors, particularly diet, physical activity, and smoking, play a critical role in the development of hypertension among coastal populations. Addressing these risk factors through targeted interventions may reduce the burden of hypertension in these communities. Keywords: risk factors, hypertension, coastal communities